Organic fertilizers diminish two important pests on collard green compared to synthetic fertilizer - Sousa, Virginia; Ursi-Ventura, Maurício; Teruhiko-Hata, Fernando; Vinícius-Constantino, Leonel (Revista Mexicana de Ciencias Agrícolas, 2024)
Plant fertilization may impact directly on insect pest behavior and biology. Fertilization may be accomplished by using synthetic mineral or organic fertilizers. The effect of different doses of boiled hen chicken manure, Penergetic®, Bokashi compound and mineral fertilizer on the adult population of Bemisia tabaci and Myzus persicae on collards leaves were evaluated. The experiment was conducted in the greenhouse using the treatments: Bokashi, Penergetic® bioactivator, 2.5%, 5%, and 7.5% of solution of boiled manure, mineral fertilization and control. The number of insects was counted directly on the leaves, and the nitrogen, potassium content, and total phenolic compound in the leaves were determined. Higher populations of Bemisia tabaci and M. persicae were observed on NPK-fertilized plants compared to other treatments. Higher levels of nitrogen foliar were found for Bokashi-fertilized plants; and higher concentrations of total phenolic compounds were found in the control. A negative correlation between total phenolics and B. tabaci was established suggesting the importance of these compounds in the species development. The results indicate the importance of the source of the fertilization for sustainable pest management.